Thursday

April 24, 2014

April 24, 2014

Posted by **michael** on Monday, June 14, 2010 at 8:53pm.

- algebra -
**MathMate**, Tuesday, June 15, 2010 at 7:52am(x-11)(x²+6x-3)

=x(x²+6x-3) - 14(x²+6x-3)

=x³+6x²-3x -14x²-84x+42

Collect like terms and add.

**Related Questions**

Algebra - Find the product: -6x(-8x^2+x+5) A)-14x^3-5x^2-x B)48x^3+x+5 C)48x^3-...

algebra - what is a quartic function with only the two real zeros given x=5 and ...

ALGEBRA - 1, Factor each expression x^2 - 10x - 24 A. (x + 4)(x - 6) B. (x + 6)(...

Algebra 2 - f(x)=(6x-6)/4 g(x)=1/x Find (f/g)(x) f(x)=6x-7 g(x)=8x-3 Find (f-g)(...

Pre-algebra - I have some practice problems, and I need to have them worked out...

Pre-algebra - I have some practice problems, and I need to have them worked out...

Math - Solve each of the following quadratic equations by completing the aquare...

Algebra - FIND THE GCF OF THE PRODUCT (3B+6)(2B-10) SOLVE... X^2=-6X x(x+6)= 0 x...

Algebra - Find two binomials whose product is x^2 - 6x + 9 and explain how you ...

geometry - need help please: the sides of the triangle on the lines 6x-7+11=0 2x...